(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article generalizes information about the state policy and legal foundations regarding the preservation of cultural heritage objects in our country, as well as the essence and significance of recent activities in this field